Work-related stress and subjective well-being: The role of affective well-being, organizational climate, and organizational identification - Silva, V. H.; Duarte, A.P.; Faustino, L. (1.ª Conferência de Saúde Societal, 2022)
The promotion of healthy workplaces, along with well-being research, has received increasing attention in recent decades. The way people feel at work has an impact both on organizational results and on overall subjective well-being (SWB). The present study aims to analyze the relationship between work-related stress and SWB based on the examination of individual factors, such as affective well-being at work and organizational identification, as well as contextual processes, such as the perception of a climate of support, as explanatory psychological processes of this relationship. The data were collected through an online survey (N= 138 workers from a Portuguese University). The results obtained show that the effect of work-related stress on SWB is fully explained by the perception of a climate of support and affective well-being at work. Contrary to what was expected, the results obtained show that organizational identification has no buffering effect on the relationships between work-related stress and affective well-being at work, nor between work-related stress and a climate of support. Taken together, the results suggest that work-related stress has an impact on individuals’ overall well-being trough the indirect pathway of a climate of support and affective well-being at work. The results are discussed considering their contribution to the development of research on the promotion of healthier workplaces, namely regarding the promotion of contexts with a positive impact on worker’s SWB.